INCREASING THE EFFECTIVENESS OF SOME TYPES OF ATTRACTANTS THROUGH SEVERAL TYPES OF DISPENSERS AGAINST FRUIT FLY PESTS (Bactrocera spp. ) ON GUAVA PLANTS (Psidium guajava L. ) - Sulaiman Ginting; S. Edy Sumantri; Fenty Maimunah Simbolon; Syamsafitri (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2021)
This research was carried out in Sawit Rejo Village, Sunggal District, Deli Serdang Regency, North Sumatra Province, at an altitude of ± 500 m above sea level. The aim of this research was to determine the effectiveness and catchability of several types of attractants and dispenser media on the attraction of fruit fly pests to guava (Psidium guajava L) . This research was carried out in 2 stages. The first stage was a Randomized Block Design with testing of several types of attractants carried out at 9 levels, namely, A1 (Synthetic Methyl Eugenol Attractant 800 g/l), A2 (Pattoouli Oil), A3 (Nutmeg Oil), A4 (Pattoouli Flower Oil) , A5 (Cinnamon Oil), A6 (Ylang Ylang Flower Oil), A7 (Citronella Oil), A8 (Lemon Oil) and A9 (Vutive Root Oil). The second stage was a Factorial Randomized Block Design by testing several types of attractants and dispenser media, with the first factor being the type of attractant with 4 levels, namely A1 (Synthetic Methyl Eugenol Attractant 800 g/l), A2 (Pattoouli Oil), A3 (A1 + Solvent Solution) , A4 (A2 + Solvent Solution). The second factor for media dispensers was carried out at 3 levels, namely K (Cotton Roll Media), B (Wooden Block Media) and P (Plastic Media). The parameters observed were the number of fruit flies trapped in the bottle in the first stage, the number of non-target insects in the first stage, the number of fruit flies trapped in the second stage, the non-target insects in the second stage and. The results of the research showed that treatment in the first stage had a significant effect on the number of fruit flies trapped. Attractant treatment with synthetic methyl eugenol and patchouli oil is the treatment that attracts most fruit flies so they become trapped in the treatment bottles. Meanwhile, in the second stage, the research results showed that treatment A1 (Synthetic Methyl Eugenol Attractant 800 g/l) was the most effective in attracting fruit fly pests , this can be seen from the results of the number of fruit flies trapped in bottles compared to other types of attractants. Meanwhile, the most effective media dispenser is media K (Cotton Roll). This can also be seen from the number of flies trapped in bottles compared to other media. Meanwhile, the treatment interaction between the type of attractant and the dispenser media which had a significant effect was the interaction between A1 (Synthetic Methyl Eugenol Attractant 800 g/l) and the dispenser medium K (Cotton Roll), this can be seen from the results of the number of fruit flies trapped in the bottle compared to other interactions. This second stage of research shows the results of a real influence with a decreasing graph. This is in accordance with research conducted from treatment 1 DSA – 25 DSA, the number of fruit fly catching abilities decreased over time.